1998
DOI: 10.1289/ehp.98106807
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neurotoxicology of endocrine disruptors and pesticides: identification of information gaps and research needs.

Abstract: There is increasing evidence that some environmental chemicals can interrupt neurodevelopmental processes during critical periods of development, resulting in effects on sensory, motor, and cognitive function. It is now generally accepted that developing organisms are differentially sensitive to chemical exposure because of toxicokinetic and/or toxicodynamic factors. Regulatory mechanisms have been implemented to protect humans from over- or inappropriate exposures to environmental chemicals. Current regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Endocrine alterations in women resulting from environmental or occupational exposure may represent increased risk for endometriosis, reproductive and other endocrinerelated cancers, or impaired oocyte competence, ovarian function or menstrual cycling (Nicolopoulou-Stamati & Pitsos 2001;Pocar et al 2003;Windham et al 2005). Effects of early life exposures to EDCs remain unclear, though it has been suggested that foetal or childhood exposure may lead to altered sex differentiation (Toppari & Skakkebaek 1998), effects on neurological and reproductive development (Tilson 1998;Teilmann et al 2002;Colborn 2004Colborn , 2006Swan et al 2005) and increased risk of reproductive problems or cancer later in life (Damgaard et al 2002;Aksglaede et al 2006;Main et al 2006a). Programming in early life can determine an individual's future health; therefore, early chemical exposures may have long-term impacts later on in life (Gluckman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine alterations in women resulting from environmental or occupational exposure may represent increased risk for endometriosis, reproductive and other endocrinerelated cancers, or impaired oocyte competence, ovarian function or menstrual cycling (Nicolopoulou-Stamati & Pitsos 2001;Pocar et al 2003;Windham et al 2005). Effects of early life exposures to EDCs remain unclear, though it has been suggested that foetal or childhood exposure may lead to altered sex differentiation (Toppari & Skakkebaek 1998), effects on neurological and reproductive development (Tilson 1998;Teilmann et al 2002;Colborn 2004Colborn , 2006Swan et al 2005) and increased risk of reproductive problems or cancer later in life (Damgaard et al 2002;Aksglaede et al 2006;Main et al 2006a). Programming in early life can determine an individual's future health; therefore, early chemical exposures may have long-term impacts later on in life (Gluckman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Generalmente, se asume que sólo las malformaciones congénitas, el retraso en el crecimiento intrauterino y la muerte embrionaria o fetal son consecuencias de la toxicidad del desarrollo. Sin embargo, defectos funcionales pueden también ser el resultado de un proceso teratogénico y en este respecto existen evidencias de que los pesticidas pueden estar induciendo toxicidad neurológica 29,30 , endocrina 31,32 e inmune 33 en niños expuestos in utero a pesticidas.…”
Section: A R T í C U L O D E R E V I S I ó Nunclassified
“…The enhanced susceptibility of the developing brain seems to depend to a great extent on disruption of sensitive processes that occur only during development when the CNS undergoes defined periods of maturation (Tilson 1998), and more data are clearly needed to elucidate the importance of a changed BBB for neonatal neurotoxicity as well as neurological dysfunction of later life.…”
Section: Susceptibility Of the Developmental Nervous Systemmentioning
confidence: 99%
“…Although the developing nervous system has some capacity to adapt to or compensate for early perturbations, there is clear evidence that the developing nervous system is more vulnerable to many chemical agents than the adult nervous system (Tilson 1998). During the transition from neuroblasts to mature neurons, cells transiently retain a substantial degree of phenotypic plasticity.…”
Section: Susceptibility Of the Developmental Nervous Systemmentioning
confidence: 99%